Reflections on neo-developmentalism in the light of the Lula's governments - Vaz, Vinicius R.C.; De Moraes, Isaías A. [UNESP] (Universidad Nacional Autonoma de Mexico, 2022)
Since the mid-2000s, the maintenance of the orthodox macroeconomic regime of the Lula's governments surprised several intellectuals in the applied social sciences sector. What marks Lula's government, especially, are two characteristics: i) the economic growth with the commodities boom or the commodities super cycle, and ii) the fight against poverty. This second phenomenon propitiated for a group of intellectuals to formulate the thesis that Brazil would be in a process of social developmentalism. On the other hand, a fraction of economists met to formulate a new theory, the new developmentalism, criticizing the process of de-industrialization, debt crisis and external dependence that occurred in Brazil. These two theoretical currents formed what some academics called neo-developmentalism. This article proposes to make a critical reflection and differentiation on the two currents.
Reflexiones sobre el neo-desarrollismo a la luz de los gobiernos de Lula
Keywords: Economic development; Latin America development; new developmentalism